The effects of sprint interval training on sail pumping performance of a male windsurfing Olympian - Hagiwara, M.; Ohya, T.; Yamanaka, R.; Onuma, H.; Suzuki, Y. (The Journal of Physical Fitness and Sports Medicine, 2017)
[Aims] This study was to determine the effects of on shore Sprint Interval Training (SIT) using a rowing ergometer on anaerobic and aerobic capacity, and sail pumping performance on water in a male windsurfing Olympian. [Methods] Training was in two phases, the first comprising nine sessions over 11 days, and one training session (repeated sets of five maximal effort rowing with 4 min recovery between each set). The second training phase comprised six sessions over 11 days, and two sessions each comprising repeated sets of eight (each set: 20 s maximal efforts rowing and 10 s rest) with a 15 min rest between sessions. [Results] The after training period were that the mean output power in the 1 min all-out rowing test increased (P<0.01), and the peak output power tended to increase. In the incremental stage test, the polygonal curve of heart rate (HR) and blood lactate concentrations (BLa) during submaximal exercise shifted to the right, the intensity of onset of blood lactate accumulation (OBLA) tended to increase, and maximal exercise intensity tended to increase. The 2000 m rowing time and mean output power tended to improve. HR decreased during the sail pumping test (P<0.01). [Conclusions] SIT using a rowing ergometer in a windsurfing Olympian improved anaerobic capacity, submaximal aerobic capacity, and maximal aerobic performance. These improvements were reflected in indirect improvement in sail pumping performance (reduced cardiorespiratory load) in light wind conditions on water.